A Critical Review on Mathematical Functions Employed for Heptane Plus Characterization in Gas Condensate Reservoirs: Lessons Learned and Future Development - Steven Chandra (Journal of Earth Energy Engineering, 2018)
Characterizing heptanes plus fraction in PVT analysis has been a complex problem since its first inception. In this publication, the author is reviewing available mathematical functions employed for this task, whilst pointing out advantages and weaknesses for each of them and proposing a new method that is capable of complex characterization. This publication addresses a new method that is capable of accurately characterize heptane plus fraction especially in discontinued areas where errors could leap up to 40%. The author modifies natural logarithmic function to be used as an accommodation to discontinuities. The modified distribution provides better accuracy in modeling the discontinuities as a straight-line function, making them ideal for real gas condensate composition characterization. The new method is tested against several test data used by previous researchers, and applied to 3 sets of field data. The results have shown that this new method is capable of lowering CPU requirement whilst making better accuracy for all test data.